2011
DOI: 10.2147/ndt.s18333
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and tolerability of open-label aripiprazole augmentation of antidepressant therapy in major depressive disorder

Abstract: Background:Effective management of major depressive disorder often includes the long-term use of multiple medications, and the longer-term utility and safety of adjunctive aripiprazole has not been evaluated in a controlled setting.Patients and methods:Patients (n = 706) completing one of two 14-week double-blind studies of aripiprazole augmentation, as well as de novo patients (n = 296) nonresponsive to current antidepressant therapy, were enrolled in this open-label study. Patients received open-label aripip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 23 publications
(24 reference statements)
5
56
0
Order By: Relevance
“…However, when we consider that the duration of most trials varied from 4 to 12 weeks, such short-term trial duration may not accurately evaluate a potential development of TD in patients with MDD. Currently, we have only two 52-week maintenance studies each in aripiprazole and quetiapine XR for MDD [50,51]. There were four spontaneous reports of TD in aripiprazole's 52-week longterm study, although all four cases resolved with dose reduction or drug discontinuation.…”
Section: Clinical Issues In the Use Of Atypical Antipsychotics In CLImentioning
confidence: 99%
“…However, when we consider that the duration of most trials varied from 4 to 12 weeks, such short-term trial duration may not accurately evaluate a potential development of TD in patients with MDD. Currently, we have only two 52-week maintenance studies each in aripiprazole and quetiapine XR for MDD [50,51]. There were four spontaneous reports of TD in aripiprazole's 52-week longterm study, although all four cases resolved with dose reduction or drug discontinuation.…”
Section: Clinical Issues In the Use Of Atypical Antipsychotics In CLImentioning
confidence: 99%
“…Although clinical experience is limited during longer-term adjunctive therapy, there is reason to be optimistic that dyskinesias will resolve if the offending medication is stopped. 22 …”
Section: Recommendations To Minimize Riskmentioning
confidence: 99%
“…One study reported the longer-term tolerability of adjunctive aripiprazole treatment in an open-label 52-week trial with 994 patients [14]. …”
Section: Aripiprazolementioning
confidence: 99%